2005
DOI: 10.1111/j.1365-2125.2005.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for drug interactions involving cytochrome P450 in patients attending palliative day care centres: a multicentre audit

Abstract: AimTo determine the potential for drug interactions involving cy tochrome P450 (CYP) in patients receiving palliative day care. MethodsDrugs used by patients attending four specialist palliative day care centres were reviewed to identify combinations that could result in a pharmacokinetic interaction via any of the five main human forms of CYP. ResultsOf 160 patients, 145 (91%) were prescribed at least one drug that was a substrate, inhibitor or inducer of one of the five main CYP isoforms. Twenty-four drug co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
0
11
0
4
Order By: Relevance
“…Many patients receiving palliative care are elderly and have several chronic conditions, resulting in the use of numerous drugs, typically 7e8 (range 1e20). 76,77 This polypharmacy increases the likelihood of drug interactions involving CYP450, with possibly 10e20% of patients receiving a combination likely to produce a clinically relevant CYPmediated interaction (Table 6). 76,77 For a longer list of commonly used drugs that are moderate-to-potent enzyme inhibitors or inducers, also see Appendix.…”
Section: Cyp450 Drugedrug Interactions In Palliative Carementioning
confidence: 99%
See 2 more Smart Citations
“…Many patients receiving palliative care are elderly and have several chronic conditions, resulting in the use of numerous drugs, typically 7e8 (range 1e20). 76,77 This polypharmacy increases the likelihood of drug interactions involving CYP450, with possibly 10e20% of patients receiving a combination likely to produce a clinically relevant CYPmediated interaction (Table 6). 76,77 For a longer list of commonly used drugs that are moderate-to-potent enzyme inhibitors or inducers, also see Appendix.…”
Section: Cyp450 Drugedrug Interactions In Palliative Carementioning
confidence: 99%
“…In one series, about 50% of the interactions involved corticosteroids, and 25% analgesics. 76 In a second series, the most frequently used inducers or inhibitors of CYP450 (and/or P-glycoprotein, or UGT) were dexamethasone, esomeprazole, omeprazole, fluconazole, ciprofloxacin, carbamazepine, carvedilol and verapamil (also see Appendix). 77 Interactions may be missed, e.g., recurrence of pain may be interpreted as disease progression rather than altered analgesic metabolism.…”
Section: Cyp450 Drugedrug Interactions In Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Statistically, it would be almost impossible for the more than 900 consecutive patient days of inpatient care reported here to have had no such events. 1,24,25 A specific subgroup of adverse events are sentinel events (Table 1). These are defined as ''an unexpected occurrence involving death or serious physical or psychological injury, or risk thereof.''…”
Section: Adverse Events In Hospice and Palliative Carediscussionmentioning
confidence: 99%
“…2 Similarly, an audit of 160 patients attending palliative daycare found that 25 drug combinations involving 35 patients could have given rise to clinically important interactions. 3 There is the challenge of applying theoretical knowledge of drug metabolising enzyme systems, such as cytochrome P450, to the clinical situation. Some predicted interactions, such as increased sedation with midazolam when coadministered with erythromycin, are clinically significant.…”
Section: General Pharmacologymentioning
confidence: 99%